Long‐term neurodevelopmental outcome in preterm infants with intraventricular haemorrhage. (15th July 2022) - Legge, Nele; Lutz, Tracey; Wocadlo, Crista; Rieger, Ingrid
Abstract : Background: Intraventricular haemorrhage (IVH) is one of the key risks for long‐term neurodevelopmental issues. There remains controversy over the impact low‐grade IVH has on the long‐term outcome of premature infants. This study describes the long‐term neurodevelopmental impact of Grade I and II IVH in former preterm infants in the early school years. Methods: This is a retrospective cohort analysis from one tertiary neonatal intensive care unit (NICU) in Australia including all infants born at <30 weeks' gestation and admitted to the NICU between 2006 and 2013 with complete ultrasound reports and follow‐up results. Results of standardised tests for neurodevelopmental outcomes at 5 and 8 years were compared between infants who suffered mild IVH and infants who had normal head ultrasounds. Results: During the study period, 491 infants <30 weeks gestation were admitted; 275 patients had full follow‐up data available. We found no significant difference in examined outcomes at 5‐ and 8‐year follow‐up. Conclusion: Mild IVH does not affect cognitive, motor and academic outcomes at school age.